2010
DOI: 10.1098/rspb.2010.1151
|View full text |Cite
|
Sign up to set email alerts
|

Individual-learning ability predicts social-foraging strategy in house sparrows

Abstract: Social foragers can use either a 'producer' strategy, which involves searching for food, or a 'scrounger' strategy, which involves joining others' food discoveries. While producers rely on personal information and past experience, we may ask whether the tendency to forage as a producer is related to being a better learner. To answer this question, we hand-raised house sparrow (Passer domesticus) nestlings that upon independence were given an individual-learning task that required them to associate colour signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 57 publications
5
48
0
Order By: Relevance
“…Additionally, a linkage between foraging tactic and learning performance has been reported in house sparrows (Passer domesticus). Sparrows that are better in associating a colour cue with a food reward were also more likely to produce in a social foraging context (Katsnelson et al 2011). Given these findings, guinea pigs that are better in learning to associate a size of an object with a reward might also be more engaged in producing during foraging.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, a linkage between foraging tactic and learning performance has been reported in house sparrows (Passer domesticus). Sparrows that are better in associating a colour cue with a food reward were also more likely to produce in a social foraging context (Katsnelson et al 2011). Given these findings, guinea pigs that are better in learning to associate a size of an object with a reward might also be more engaged in producing during foraging.…”
Section: Discussionmentioning
confidence: 96%
“…Many vocalising bird and cetacean species 28 acquire their vocalisations during a juvenile sensitive period [7,86]. In humans, field studies have 29…”
Section: Age Differences 25mentioning
confidence: 99%
“…Others have found that performance in an asocial learning task subsequently 115 predicts social information use, although again in opposite directions: two studies found that better 116 individual learners were more likely to use social information [41,42], two studies that they were 117 less likely [43,44]. Three studies with humans have linked social learning to relatively stable 118 individual differences, specifically social dominance [45], collectivism [46] and IQ [47].…”
mentioning
confidence: 99%
“…Furthermore, asocial individuals might be more likely to disperse from groups [35] and thus not only be alone, but also be in novel environments where rapid individual learning can be critical for survival [35]. These differences in cognitive style can translate into different social roles; for example, in house sparrows, the tendency to be a producer (to find food) rather than a scrounger (use social information) is positively associated with individual learning ability [36].…”
Section: Personality and Individual Differences In Cognitive Stylementioning
confidence: 99%